Punishment For Motor Vehicle Theft With Violence (Judgment No. 596/Pid.B/2023/PN Jkt.Brt) - Nadya Nadzifatur Rahma; Siti Marwiyah; M. Yustino Aribawa; Bachrul Amiq; Wahyu Prawesthi (CV. AFDIFAL MAJU BERKAH, 2026)
This article analyzes the judicial reasoning in West Jakarta District Court Decision No. 596/Pid.B/2023/PN Jkt.Brt concerning motor vehicle theft with violence, with a focus on the defendant’s attempt to distance himself from the violent elements of the crime. Such a defense strategy is conceptually parallel to exoneration clauses in contract law, which seek to exclude or limit liability. Through the lens of Radbruch’s triadic values of law justice, legal certainty, and utility, the study highlights the contradictions arising from the judicial rejection of exoneration claims in collective violent crimes. While exoneration clauses serve to ensure fairness and proportionality in civil contexts, their transposition into criminal law risks undermining deterrence and public order. Empirical observations reveal inconsistent judicial interpretations in Indonesia, compounded by institutional limitations and lack of specialized consumer or criminal law adjudication. Comparative insights from the European Union and Australia underscore the importance of regulatory clarity and strict enforcement to safeguard fairness in contractual and criminal contexts alike. The article concludes by proposing a normative framework for reform that emphasizes clearer sentencing guidelines, statutory restrictions on exoneration in collective crimes, and alignment with international best practices. These findings contribute to the ongoing discourse on balancing fairness, legal certainty, and public protection in Indonesian criminal law.